Effect of finisher diets of different crude protein levels on carcass yield and abdominal fat pads of roaster chickens raised on tri-phase feeding regime - Meremikwu, V.N (Nigerian Journal of Animal Science, 2023)
Excessive fat deposition in poultry carcass can reduce carcass and processing yields especially in broiler chickens, hence the need to reduce it through dietary manipulations. One hundred and twenty finisher broilers were used to investigate the effect of different crude protein levels on carcass yield and abdominal fat pads of roasters raised on tri-phase feeding regime. The feeding trial comprised of a starter phase (0-4 weeks), a grower phase (4-8 weeks) and a finisher phase (8-12 weeks) on broiler finisher diets of varying crude protein levels. Treatment (T1) (control) had no restriction but fed commercial finisher diet from 4-12 weeks after brooding. T 2 (four weeks growth restriction on grower diet after brooding and finishing to 12 weeks on 18% crude protein. T3 (four weeks growth restriction on grower diet after brooding and finishing to 12 weeks on 19% crude protein . T4 (four weeks growth restriction on grower diet after brooding and finishing to 12 weeks on 20% crude protein . Two birds per replicate were slaughtered at twelve weeks of age to evaluate the carcass and internal organs. Restricted groups on 18% CP had significantly higher carcass yield. Abdominal fat was significantly higher in the control. Carcass yield of growth-restricted roasters was influenced by crude protein levels of the finisher diets while abdominal fat was reduced by both restriction to retard growth and the high fiber content of the grower and finisher diets. 19 and 20% crude protein levels in finisher diets with high fibre content produced low carcass weight in nutrient/growth restricted broilers.